Analysis Of Islamic Banking Financial Performance Before And After The Merger - Irma Juniar Frestiva; Muhammad Sholahuddin (UNIVED Press, 2024)
This research aims to analyze the financial performance of Islamic banking, namely BNI Syariah, BRI Syariah, and Bank Syariah Mandiri, both before and after the merger process that resulted in the formation of the new Bank Syariah Indonesia. The time period to be examined in this study encompasses the years between 2019 and 2023, with the goal of obtaining a comprehensive and detailed overview of changes in financial performance over time. The researcher will employ a quantitative approach involving the collection and analysis of numerical data. The variables to be used in this study will include financial ratios that have a close relationship with the profitability and risks experienced by Islamic banks. The research findings indicate differences in the financial performance of Islamic banking before and after the merger.